Identification of Differentiation-Related Proteins in Gastric Adenocarcinoma Tissues by Proteomics. (October 2016) - Zhou, Xin; Yao, Kun; Zhang, Lang; Zhang, Ying; Han, Yin; Liu, Hui-Ling; Liu, Xiang-Wen; Su, Gang; Yuan, Wen-Zhen; Wei, Xiao-Dong; Guan, Quan-Lin; Zhu, Bing-Dong
There is a significant correlation between the degree of tumor differentiation and the survival of patients with gastric cancers. In this report, we compared proteomic differences between poorly differentiated gastric adenocarcinoma tissues and well-differentiated gastric adenocarcinoma tissues in order to identify differentiation-related proteins that may be closely correlated with differentiation of gastric cancer pathogenesis. We identified 7 proteins, of which calreticulin precursor, tapasinERP57 heterodimer, pyruvate kinase isozymes M1/M2 isoform M2, class Pi glutathione S-transferase, and chain A crystal structure of human enolase 1 were upregulated in poorly differentiated gastric adenocarcinoma compared with well-differentiated gastric adenocarcinoma, while myosin-11 isoform SM2A and actin alpha cardiac were downregulated. Two of them, pyruvate kinase isozymes M1/M2 isoform M2 and enolase 1 are enzymes involved in glycolytic pathway. The upregulation of pyruvate kinase isozymes M1/M2 isoform M2 and enolase 1 in poorly differentiated gastric adenocarcinoma was confirmed by Western blotting and immunohistochemistry. Furthermore, we observed 107 cases with gastric adenocarcinoma and found that the high expression of pyruvate kinase isozymes M1/M2 isoform M2 and enolase 1 correlates with tumor size ( P = .0001 and P = .0017, respectively), depth of invasion ( P = .0024 and P = .0261, respectively), and poor prognosis of patients. In conclusion, with this proteomic analysis, pyruvate kinase isozymes M1/M2 isoform M2 and enolase 1 were identified upregulated in poorly differentiated gastric adenocarcinoma comparing with well-differentiated gastric adenocarcinoma. The expression level of pyruvate kinase isozymes M1/M2 isoform M2 and enolase 1 was significantly correlated with overall survival. Some of them would be differentiation-related cancer biomarkers and are associated with tumor metastasis, invasion, and prognosis.